Energy-Efficiency-Oriented Vision Feedback Control of QCSP Systems: Linear ADRC Approach - Li, Shengming; Feng, Lin (Frontiers in Energy Research, 2022)
How to save the energy of unmanned aerial vehicles (UAVs), and then enable long-distance transport is a very real and difficult task. However, for UAVs, the classical object detection algorithm, such as the deep convolutional neural network-based target detection algorithm, and the classical flight control algorithm, such as the PID-based position control algorithm, require significant energy, which limits the application scenarios of the UAV system. In view of this problem, this paper proposes a lightweight object detection network and a linear active disturbance rejection controller (LADRC) for the quadrotor with the cable-suspended payload (QCSP) system to improve energy efficiency. The system uses a YOLOV3 network and embeds it into the Jesson NX mobile platform to accurately detect the target position. Furthermore, a non-linear velocity controller with a cable-suspended structure to control the velocity of the payload, a LADRC algorithm is adopted to achieve fast and accurate control of the payload position. Simulations and real flight experiments show that the proposed object detection algorithm and the LADRC control strategy can save the energy of drone effectively.